2018
DOI: 10.3389/fpls.2018.00367
|View full text |Cite
|
Sign up to set email alerts
|

Defective APETALA2 Genes Lead to Sepal Modification in Brassica Crops

Abstract: Many vegetable and oilseed crops belong to Brassica species. The seed production of these crops is hampered often by abnormal floral organs, especially under the conditions of abiotic conditions. However, the molecular reasons for these abnormal floral organs remains poorly understood. Here, we report a novel pistil-like flower mutant of B. rapa. In the flower of this mutant, the four sepals are modified to one merged carpel that look like a ring in the sepal positions, enveloping some abnormal stamens and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…ERTF10 and ERDBF3 showed the highest expression in pistil and the lowest in stamen. AP2 has been reported in other crops to be important for flower and seed development (Jofuku et al, 1994;Zhang et al, 2018). In this study, the expression level of AP2 was found to be higher in the reproductive organ stamen, male calyx, female calyx, pistil, and ovary compared to that in leaf (Fig.…”
Section: Expression Levels Of Ethylene Candidate Genes In Different Flower Structuressupporting
confidence: 50%
“…ERTF10 and ERDBF3 showed the highest expression in pistil and the lowest in stamen. AP2 has been reported in other crops to be important for flower and seed development (Jofuku et al, 1994;Zhang et al, 2018). In this study, the expression level of AP2 was found to be higher in the reproductive organ stamen, male calyx, female calyx, pistil, and ovary compared to that in leaf (Fig.…”
Section: Expression Levels Of Ethylene Candidate Genes In Different Flower Structuressupporting
confidence: 50%
“…Hooked sepals are commonly encountered in broccoli hybrids, resulting in a non-uniform crown surface and a reduced ability to shed water. In B. rapa , Zhang et al (2018) identified loss-of-function BrAP2 alleles with sepal defects similar to the hooked sepal phenotype observed in BolTBDH. In BolTBDH, the optimal MQM model for hooked sepals (SH ∼ 1@2.1 + [1@0.2 × 1@20.2]) co-localized with the bud morphology hotspot Bud 1 .…”
Section: Discussionmentioning
confidence: 53%
“…In BolTBDH, the optimal MQM model for hooked sepals (SH ∼ 1@2.1 + [1@0.2 × 1@20.2]) co-localized with the bud morphology hotspot Bud 1 . Bud 1 QTL include the homologous candidates AP2 (Bo1g004960), in agreement with Zhang et al (2018). Further evaluation of AP2 (Bo1g004960) homologs and other floral developmental candidates ( Table 6 ) in the Bud 1 hotspot may prove useful for improvement of bud morphology traits.…”
Section: Discussionmentioning
confidence: 67%
“…Our study showed that these 7 GmAP2 genes were expressed in flowers ( Figure 3 ) and were able to rescue the defective phenotype of ap2-6 mutant, but their over-expression did not produce excess floral organs ( Supplementary Figure S7 ), indicating that they retained partially conserved function in floral organ identity. Other studies showed that many AP2 orthologs in other species were also expressed in floral organs; and the mutation of AP2 orthologs led to the defective floral organ, and their over-expression produce excess floral organs; these AP2 orthologs generally rescue the defective phenotype of floral organ identity in the Arabidopsis ap2 mutant ( Keck et al, 2003 ; Nilsson et al, 2007 ; Liu et al, 2012 ; Luo et al, 2012 ; Yan et al, 2012 ; Zhang et al, 2018 ). Therefore, the AP2 genes of different plant species, including these 7 GmAP2 genes, may share conserved roles in floral organ identity.…”
Section: Discussionmentioning
confidence: 97%